Simultaneously Mapping and Superimposing Landmark Configurations with Parsimony as Optimality Criterion - Catalano, Santiago Andres (2012)
All methods proposed to date for mapping landmark configurations on a phylogenetic tree start from an alignment generated by methods that make no use of phylogenetic information, usually by superimposing all configurations against a consensus configuration. In order to properly interpret differences between landmark configurations along the tree as changes in shape, the metric chosen to define the ancestral assignments should also form the basis to superimpose the configurations. Thus, we present here a method that merges both steps, map and align, into a single procedure that (for the given tree) produces a multiple alignment and ancestral assignments such that the sum of the Euclidean distances between the corresponding landmarks along tree nodes is minimized. This approach is an extension of the method proposed by Catalano et al. (2010. Phylogenetic morphometrics (I): the use of landmark data in a phylogenetic framework. Cladistics. 26:539–549) for mapping landmark data with parsimony as optimality criterion. In the context of phylogenetics, this method allows maximizing the degree to which similarity in landmark positions can be accounted for by common ancestry. In the context of morphometrics, this approach guarantees (heuristics aside) that all the transformations inferred on the tree represent changes in shape. The performance of the method was evaluated on different data sets, indicating that the method produces marked improvements in tree score (up to 5% compared with generalized superimpositions, up to 11% compared with ordinary superimpositions). These empirical results stress the importance of incorporating the phylogenetic information into the alignment step.